2000
DOI: 10.1063/1.126642
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature lasing via ground state of current-injected vertically aligned InP/GaInP quantum dots

Abstract: We report room-temperature injection lasing of self-assembled InP/GaInP quantum dots. Stimulated emission occurs via the ground state at λ=728 nm for cavities as short as 0.5 mm. Threshold current densities of 2.3 kA/cm2 and external differential quantum efficiencies of 8.5% have been measured for 2 mm long devices. Light output power as high as 250 mW without saturation effects can be reached in pulsed excitation. Analysis of temperature-dependent laser emission indicates the thermal coupling of charge carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…͓DOI: 10.1063/1.1539544͔ InP quantum dots ͑QDs͒ and GaInP quantum wells exhibit strong light emission in the visible spectrum of interest for optoelectronic applications, 1,2 where the polarization properties are used in, for instance, light emitting diodes. The islands, which form during overgrowth of InP quantum dots, were studied using scanning tunneling luminescence ͑STL͒ and photoluminescence ͑PL͒.…”
Section: Luminescence Polarization Of Ordered Gainpõinp Islandsmentioning
confidence: 99%
“…͓DOI: 10.1063/1.1539544͔ InP quantum dots ͑QDs͒ and GaInP quantum wells exhibit strong light emission in the visible spectrum of interest for optoelectronic applications, 1,2 where the polarization properties are used in, for instance, light emitting diodes. The islands, which form during overgrowth of InP quantum dots, were studied using scanning tunneling luminescence ͑STL͒ and photoluminescence ͑PL͒.…”
Section: Luminescence Polarization Of Ordered Gainpõinp Islandsmentioning
confidence: 99%
“…[1][2][3][4][5] The InP/Ga x In 1Ϫx P system exhibits strong emission of light in the longer wavelength region of the visible spectrum and is thus interesting for several applications. [6][7][8] However, the Ga x In 1Ϫx P alloy has a very complex nature both structurally and optically. Transmission electron microscopy 9 ͑TEM͒ and scanning tunneling microscopy 10 ͑STM͒ investigations have shown that under certain conditions atomic long-range ordering may occur in the Ga x In 1Ϫx P alloy.…”
Section: Introductionmentioning
confidence: 99%
“…1 The interest stems from both science and technology, which have involved QD's in studies of the fundamental properties as well as for building blocks in optoelectronic devices. 2,3 The local environment of a QD has a considerable impact on the electronic structure both in terms of strain and confinement. Consequently, the effects of a thin capping layer have been investigated for a variety of QD systems, such as InAs/GaAs, 4 -7 InGaAs/GaAs, [8][9][10] InSb/InP, 11 CdSe/ZnSe, 12 SiGe/Si, 13,14 and InP/GaInP.…”
Section: Introductionmentioning
confidence: 99%